Calculation of ventilation rates and ammonia emissions: Comparison of sampling strategies for a naturally ventilated dairy barn. (October 2020) - Janke, David; Willink, Dylia; Ammon, Christian; Hempel, Sabrina; Schrade, Sabine; Demeyer, Peter; Hartung, Eberhard; Amon, Barbara; Ogink, Nico; Amon, Thomas
Abstract : Emissions and ventilation rates (VRs) in naturally ventilated dairy barns (NVDBs) are usually measured using indirect methods, where the choice of inside and outside sampling locations (i.e. sampling strategy) is crucial. The goal of this study was to quantify the influence of the sampling strategy on the estimation of emissions and VRs. We equipped a NVDB in northern Germany with an extensive measuring setup capable of measuring emissions under all wind conditions. Ammonia (NH3 ) and carbon dioxide (CO2 ) concentrations were measured with two Fourier-transform infrared spectrometers. Hourly values for ventilation rates and emissions for ammonia over a period of nearly a year were derived using the CO2 balance method and five different sampling strategies for the acquisition of indoor and outdoor concentrations were applied. When comparing the strategy estimating the highest emission level to the strategy estimating the lowest, the differences in NH3 emissions in winter, transition, and summer season were +26%, +19% and +11%, respectively. For the ventilation rates, the differences were +80%, +94%, and 63% for the winter, transition and summer season, respectively. By accommodating inside/outside concentration measurements around the entire perimeter of the barn instead of a reduced part of the perimeter (aligned to a presumed main wind direction), the amount of available data substantially increased for around 210% for the same monitoring period. Highlights: Sampling strategy influences the estimation of NH3 and ventilation rates. Maximum difference in sampling strategies for NH3 estimation was 26%. Maximum difference in sampling strategies for ventilation rate estimation was 94%. A sampling line in the middle of the barn does not provide extra information. Measuring around the entire perimeter of the barn increased the dataset up to 210%.